U.S. policy toward China : an introduction to the role of interest groups - Sutter, Robert G. (Lanham : Rowman & Littlefield, 1998)
Includes index
Keywords: Pressure groups -- United States. -- History -- 20th century; China -- Foreign relations -- United States..; United States -- Foreign relations -- China